Using Fuzzy Bang-Bang Relay Controller for a Single-Axis Magnetic Bearing System - Rashidifar, Mohammad Amin; Rashidifar, Ali Amin (Asian Review of Mechanical Engineering, 2014)
This paper presents a new type of fuzzy controller for active magnetic bearing applications. Active magnetic bearing (AMB) applications in rotating machinery are fast growing due to their precise and contact less support of the rotating shaft. AMB are open loop unstable due to nonlinear relationship between electromagnetic force,attraction distance and the electromagnetic current. To regulate the electromagnetic forces acting on the bearing, external control is required. Feedback control for AMB systems such as proportional and derivative is only restricted to linearized region. For nonlinear control systems, artificial intelligence techniques such as fuzzy and hybrid techniques are being investigated. Bang-bang control is an old but effective technique to control nonlinear system in optimal time. Bang-bang control combined with fuzzy logic decision-making flexibility results in a robust control system. In this work an integrated fuzzy bang-bang relay controller (FBBRC) is presented to control the AMB system. FBBRC is simple to design than conventional fuzzy controllers. Comparison with other widely used AMB control techniques demonstrate improved results.